Mites as a Potential Path for Ce-Ti Exposure of Amphibians - Jacinto-Maldonado, Mónica; Meza-Figueroa, Diana; Pedroza-Montero, Martín; Lesbarrères, David; Robles-Morúa, Agustín; Navarro-Espinoza, Sofía; González-Grijalva, Belem; Pérez-Segura, Efrén; Silva-Campa, Erika; Angulo-Molina, Aracely; Paredes-León, Ricardo (Frontiers in Environmental Science, 2022)
Despite the documented effects on human and animal health, particles smaller than 0.1 µm in diameter in soils, sediments, and the atmosphere remain unregulated. Cerium and titanium oxide nanoparticles associated with traffic increase mortality, cause behavioral changes, and inhibit the growth in amphibians. Mites on the genus Hannemania live in the soil in their early stages before becoming exclusive parasites of amphibians. Unlike other mites, Hannemania is found inside the epidermis of amphibians, thus facilitating the intake of particles, and leading to direct and chronic exposure. We sampled amphibians hosting mites in a river potentially polluted by traffic sources to understand this exposure path. First, the particles collected from mites were studied by scanning electron microscopy and Raman spectroscopy. Then, sediment samples were collected and analyzed for total metal content by portable X-ray fluorescence. Our results showed that sediment samples had significant correlations (p<0.05) between elements commonly linked to catalytic converters (Zr, Mn, Ti, Nb, Fe) and Zr-Ti contents that exceeded the local geochemical background, thus suggesting an anthropic origin. While the particles adhered to mites exhibited the characteristic Raman vibrational modes of ceria (CeO2, 465 cm-1), ceria-zirconia (CeO2-ZrO2, 149, 251, and 314 cm-1), and rutile (TiO2, 602 cm-1), pointing out to the deterioration of catalytic converters as the most likely source. This research highlights the importance of traffic as a relevant source of ultrafine Ce-Ti particles and mites as a potential for chronic exposure to amphibians.